It takes two to tango: The role of customer empathy and resources to improve the efficacy of frontline employee empathy. (September 2020) - Ngo, Liem Viet; Nguyen, Thi Nguyet Que; Tran, Nam The; Paramita, Widya
Abstract: This study investigates the link between employee empathy and customer satisfaction. Building on social exchange theory, we develop a model of employee-customer empathy. We focus on the central role of customer-oriented behaviour in explaining the empathy-satisfaction relationship, predicting that employee empathy positively influences customer-oriented behaviour, which in turn enhances customer-satisfaction. We also examine the moderating roles of customer empathy, as well as of customer resources. Results of a dyadic-survey study of 211 pairs of frontline employees and their customers support the proposed moderated -mediation model. Theoretical and practical implications are discussed.